Structural and functional 3D mapping of skin tumours with non‐invasive multispectral optoacoustic tomography. Issue 2 (2nd November 2016) - Chuah, S. Y.; Attia, A. B. E.; Long, V.; Ho, C. J. H.; Malempati, P.; Fu, C. Y.; Ford, S. J.; Lee, J. S. S.; Tan, W. P.; Razansky, D.; Olivo, M.; Thng, S.
Abstract : Background: Recent advances in technology have enabled the development of various non‐invasive skin imaging tools to aid real‐time diagnosis of both benign and malignant skin tumours, minimizing the need for invasive skin biopsy. Multispectral optoacoustic tomography (MSOT) is a recently developed non‐invasive imaging tool, which offers the unique capacity for high resolution three dimensional (3D) optical mapping of tissue by further delivering highly specific optical contrast from a depth of several millimetres to centimetres in living tissues. MSOT enables volumetric, spectroscopic differentiation of tissue, both in vivo and in real time, with and without the application of biomarker‐specific probes, and is further able of providing spatial maps of skin chromophores, as well as underlying blood vasculature. Methods: Three patients with suspicious skin tumours consented to have their lesions imaged with MSOT prior to excision. The histological findings and measurements were compared. Results: We demonstrated the first in vivo clinical use of MSOT for 3D reconstruction of skin tumours in three patients with good histological correlation. Conclusion: Our findings confirm the potential benefit of the new imaging method in guiding surgical intervention to achieve a more precise excision with better clearance and lower relapse rates. It can also potentially help to shorten the duration of Mohs' micrographic surgery. Further large‐scale studies are necessary to ensure correlation between MSOT and histology.